Modeling of a 2×2 electro-optic Mach-Zehnder Interferometer optical switch with s-bend arms - Singh, G.; Janyani, V.; Yadav, R.P. (Photonics Letters of Poland, 2011)
In this paper, we present a 2×2 electro-optic switch based on a Mach-Zehnder interferometer (MZI) with tapered (s-bend) interferometric arms. All structures have been designed with a channel profile of titanium indiffused lithium niobate waveguides. The crosstalk analysis of the switch suggests that the crosstalk levels become worse (-12dB) when both interferometric arms of the structure are tapered. We have optimized the structure in order to reduce the overall switch losses (< 0.5dB) and to achieve the best possible extinction ratio (> 20dB). Full Text: PDF References: N. Agrawal et al., "Fast 2×2 Mach-Zehnder optical space switches using InGaAsP-InP multiquantum-well structures", IEEE Phot. Techn. Lett. 7, 644 (1995). [CrossRef] H.Y. Wong et al., "Monolithically integrated InGaAs-AlGaInAs Mach-Zehnder Interferometer optical switch using quantum-well intermixing", IEEE Phot. Techn. Lett. 17, 783 (2005). [CrossRef] K. Suzuki, et al., "High-Speed Optical 1 × 4 Switch Based on Generalized Mach?Zehnder Interferometer With Hybrid Configuration of Silica-Based PLC and Lithium Niobate Phase-Shifter Array", IEEE Phot. Techn. Lett. 19, 674 (2007). [CrossRef] G.Singh, R.P. Yadav, V. Janyani, Int. J. Comp. Appl. 33, 36 (2011). [CrossRef] K. Noguchi, "Ultra-high-speed LiNbO3 modulators", J. Opt. Fiber Commun. Rep. 4, 1 (2007). [CrossRef] A.M. Prokhorov, S. Yu, Physics and Chemistry of Crystalline Lithium Niobate (Hilger, New York 1990). W.-Y. Hwang et al., "Polymeric 2×2 electrooptic switch consisting of asymmetric Y junctions and Mach-Zehnder interferometer", IEEE Phot. Techn. Lett. 9, 6 (1997). [CrossRef] G. Ducournau, O. Latry, M. Kétata, "Fiber-based Mach-Zehnder interferometric structures: principles and required characteristics for efficient modulation format conversion ", Proc. of SPIE 6019, 60190A, (2005). [CrossRef] P.J. Dong et al., Peleton Photonic Systems Inc., US Patent 6763155 B2, July 13th, 2004. G.I. Papadimitriou et al., "Optical switching: switch fabrics, techniques, and architectures", J. Lightw. Techn. 21, 384 (2003). [CrossRef] OptiBPM, Waveguide optics modeling software system, version 8.0, second edition, Optiwave Inc. 2006.